Kilka uwag na temat oceny prawdomówności wypowiedzi w procesie karnym - Sznajderska, Ewelina Izabela (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article addresses the issue of lie and its detection in criminal proceedings, with particular focus on evaluating truthfulness and credibility of utterances made by the participants in criminal proceedings. It is a relatively new area of research which is of a significant importance for establishing the truth both in inquiry and in court practice. An application of new information technology solutions such as, inter alia, e-minutes serves this purpose.
Keywords: prawda; kłamstwo; ocena prawdziwości i wiarygodności; postępowanie karne; e-protokoły